Effect of Dosage and Type Liquid Organic Fertilizer on Availability N and Cu in Soil and Growth Chilli Plant (Capsicum annuum L.) - Siram Solecha, Maratus; Sasongko, Purnomo Edi; Mindari , Wanti (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Liquid Organic Fertilizer (LOF) uses livestock manure such as chickens, goats, and cows to support the growth of Red Chillies (Capsicum annuum L.) in the form of N and Cu nutrients. This research aims to determine the type of LOF that provides the best chili production results. Method: This research was designed using the Completely Randomized Design (CRD) technique, which consists of two factors. The first factor is the types of animal manure fertilizer with three levels, namely chicken (K1), goat (K2), and cow (K3). The second factor is concentrations of animal manure fertilizer with three levels, namely 5 ml/L (A1), 10 ml/L (A2), and 15 ml/L (A3). Each treatment was repeated 3 times so that there were 3x3x3=27. A control was added as a comparison, which was repeated 3 times, so the total treatment was 30 experimental units. Results: The results showed that LOF K2A3 treatment provided the highest value for total soil Cu and Cu uptake in the roots and stems of chili plants. The LOF K1A3 treatment showed the highest value in soil N-total, and LOF K1A2 gave the highest results in N uptake in the roots of chili plants. The control treatment gave the highest results in plant height, the weight of chili fruit, and the number of chili. Conclusion: Chicken manure LOF treatment with a concentration of 15 ml/L provided the highest results in soil N-total, and at a concentration of 10 ml/L provided the highest results in N absorption in the roots of chili plants.